Challenges of Ergonomics In Hospitals : A Literature Review on The Prevention of Injuries and Work Fatigue - Gherice E. Serumena; Yatna Suhendi; Mirza Nafaru Haqa (Universitas Malahayati, 2026)
ABSTRACT Hospitals are complex work environments with a variety of ergonomic challenges. Medical personnel are often exposed to high workloads in static positions and long periods of time due to the use of medical tools and equipment that are not optimally ergonomic. In Indonesia, the prevalence of ergonomics-related diseases is 11.9% with 24.7% of diagnoses and symptoms. In addition, previous research has only focused on one aspect of ergonomics such as musculoskeletal injuries without looking at the relationship between other ergonomic factors thoroughly. The novelty of this research lies in its comprehensive approach in reviewing ergonomics challenges in hospitals. This study identifies ergonomic factors that contribute to workplace injuries and fatigue, as well as develops basic methods to analyze and address the problem of injuries and work fatigue that risk reducing worker productivity and welfare. This study uses a problem identification method based on the PICO (population. intervention, comparison, outcome) approach in order to produce a more targeted and selective study starting from the formulation of research problems and objectives, literature search strategies, literature selection and screening, data extraction, data analysis and synthesis as well as the preparation of reports and publications. This study shows that increased ergonomics knowledge and the application of proper working postures contribute to work efficiency and worker well-being. Unergonomic posture has been shown to be directly related to fatigue and low back pain. The shift work system also affects the health of workers. Overall, ergonomics has an important role to play in preventing injury and fatigue, as well as improving workers' productivity and quality of life. A literature review shows that ergonomics challenges in hospitals include three interrelated physical, cognitive, and psychosocial dimensions that affect the health and performance of medical personnel. The risk of musculoskeletal injuries, mental fatigue, and emotional stress is often triggered by unergonomic work schedules, high workloads, unsupportive environmental design, and lack of a humane work system. Comprehensive ergonomics interventions including physical design adjustments, educational training, and organizational policies have been proven to be effective in reducing work complaints by 30-50%. The success of the intervention is highly dependent on management support, program sustainability, and the active participation of medical personnel. Therefore, the systematic and integrated application of ergonomics is crucial to create a safe, comfortable, and productive hospital work environment. Keywords: Ergonomics, Hospital, Workload, Injury, Fatigue. ABSTRAK Rumah sakit merupakan lingkungan kerja yang kompleks dengan berbagai tantangan ergonomi. Tenaga medis sering terpapar beban kerja yang tinggi dalam posisi statis dan waktu yang lama karena menggunakan alat dan peralatan medis yang tidak ergonomis secara optimal. Di Indonesia prevalensi penyakit yang berhubungan dengan ergonomi yaitu 11,9% dengan diagnosis dan gejala sebanyak 24,7%. Selain itu penelitian terdahulu hanya berfokus pada satu aspek ergonomi seperti cedera muskuloskeletal tanpa melihat keterkaitan antara faktor ergonomic lainnya secara menyeluruh. Kebaruan penelitian ini terletak pada pendekatan komprehensif dalam meninjau tantangan ergonomi di rumah sakit. Penelitian ini mengidentifikasi faktor-faktor ergonomi yang berkontribusi terhadap cedera dan kelelahan di tempat kerja, serta mengembangkan metode dasar untuk menganalisis dan mengatasi permasalahan cedera dan kelelahan kerja berisiko menurunkan produktivitas maupun kesejahteraan pekerja. Penelitian ini menggunakan metode identifikasi masalah berbasis pendekatan PICO (population. intervention, comparison, outcome) agar dapat menghasilkan kajian yang lebih terarah dan selektif mulai dari perumusan masalah dan tujuan penelitian, strategi pencarian literatur, seleksi dan penyaringan literature, ekstraksi data, analisa dan sintesis data serta penyusunan laporan dan publikasi. Penelitian ini menunjukkan bahwa peningkatan pengetahuan ergonomi dan penerapan postur kerja yang tepat berkontribusi pada efisiensi kerja dan kesejahteraan pekerja. Postur tidak ergonomis terbukti berhubungan langsung dengan kelelahan dan low back pain. Sistem kerja shift juga memengaruhi kesehatan pekerja. Secara keseluruhan, ergonomi memiliki peran penting dalam mencegah cedera dan kelelahan, serta meningkatkan produktivitas dan kualitas hidup pekerja. Tinjauan literatur menunjukan bahwa tantangan ergonomi di rumah sakit mencakup tiga dimensi fisik, kognitif, dan psikososial yang saling berkaitan dalam memengaruhi kesehatan an kinerja tenaga medis. Risiko cedera musculoskeletal, kelelahan mental, hingga stres emosional banyak dipicu oleh pstur kerja tidak ergonomis, beban kerja tinggi, desain lingkungan yang kurang mendukung, serta kurangnya sistem kerja yang humanis. intervensi ergonomi yang menyeluruh meliputi penyesuaian desain fisik, pelatihan edukatif, dan kebijakan oranisasional terbukti efektif mengurangi keluhan kerja hingga 30-50%. Keberhasilan intervensi sangat bergantung pada dukungan manajemen, keberlanjutan program, serta partisipasi aktif tenaga medis. oleh karena itu, penerpan ergonomi secara sistematik dan terintegrasi sangat krusial untuk menciptakan lingkungan kerja rumah sakit yang aman, nyaman, dan produktif. Kata Kunci: Ergonomi, Rumah Sakit, Beban Kerja, Cedera, Kelelahan.